The Effect of TGT Model on Student Cognitive Learning Outcomes: The Concept of Relay Running - Albertus Fenanlampir (AL-ISHLAH: Jurnal Pendidikan, 2021)
TGT cooperative type learning, as a game-based learning methodology, provides opportunities for students to develop skills in group interactions in small groups and work together with others. The world of learning today needs phenomena like this. This study aimed to determine the effect of the TGT cooperative type learning model on students' cognitive learning outcomes on the topic of relay running. This quantitative study was a quasi-experimental pretest-posttest design. The samples involved were 70 students from two different experimental and control classes. The data collection instrument in this study was 10 essay test questions validated and tested. The results showed an effect of the TGT cooperative type learning model on students' cognitive learning outcomes. The achievement test score for the TGT group was 81.67, while the control group was 75.75. It implies that the TGT group performed superior in cognitive learning outcomes when compared to the control group. Thus, it is concluded that the TGT cooperative type learning model can be recommended in improving students' cognitive learning outcomes on the concept of relay running.